Disasters and loss of life: New evidence on the effect of disaster risk management governance in Latin America and the Caribbean - Roberto Guerrero Compeán; Sergio Lacambra Ayuso (Inter-American Development Bank (IDB), 2020)
This study provides new empirical evidence on the effect of improving the conditions in disaster risk management (DRM) governance in terms of human losses resulting from disaster events. To measure governance in disaster risk management, we use the Index of Governance and Public Policy in Disaster Risk Management (IGOPP), developed by the Inter-American Development Bank, which characterizes the development of regulatory, institutional and budgetary processes for disaster risk management at the national level. This analysis uses regression models of count data for 26 countries in Latin America and the Caribbean for the 1980-2017 period. We show that an improvement in disaster risk management governance leads to a significant reduction in the probability of human losses caused by disasters triggered by natural hazards. Specifically, an additional point in the IGOPP is associated with a 3% reduction of the fatalities caused by disasters. In addition, we find that a categorical improvement from low to good disaster risk management governance conditions yields savings, in terms of avoided human fatalities, in the order of US 381-670 million per year and reduces the probability of fatality occurrence in 11 percentage points. These results suggest that the creation of conditions to improve disaster risk management governance is a crucial element not only to reverse the negative impact of the underlying causes of social vulnerability, such as deficiencies in the economic system and weak institutional capacity, but also a cost-effective strategy to reduce risk.
Keywords: Q1; Q54; Q58; 330; disaster risk management; governance; Latin America